Master batch containing down-conversion material, TPO waterproof material as well as preparation method and application of TPO waterproof material
By using downconversion materials in TPO waterproof coils, UV light is converted into visible light, and using high refractive index fillers to reflect light, combined with the synergistic effect of light stabilizers, the temperature increase and aging of TPO waterproof coils under ultraviolet irradiation is solved. The problem of this achieves better weather resistance and anti-aging performance.
Patent Information
- Application Number
- CN202411233284.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-10
AI Technical Summary
When existing TPO waterproof coils are used outdoors, the temperature rises due to ultraviolet irradiation, which accelerates the aging of the material. Although existing antioxidants and fillers can resist ultraviolet rays, they can easily increase the temperature of the material and thus accelerate the aging.
Masterbatches containing downconversion materials are used to convert UV light into visible light through downconversion materials, and combined with high refractive index fillers to reflect light to avoid temperature increase. At the same time, light stabilizers are added to synergistically reduce the temperature and aging of the TPO system.
Effectively resist UV light, avoid the temperature rise of TPO material, delay the aging process, and improve the comprehensive performance of TPO waterproof coils.
Smart Images

Figure BDA0005026940290000021 
Figure BDA0005026940290000022 
Figure BDA0005026940290000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of TPO waterproofing coiled materials, and more particularly to a master batch containing a down-conversion material, a TPO waterproofing material, and a preparation method and application thereof. Background Art
[0002] Thermoplastic polyolefin (TPO) waterproofing membrane has excellent comprehensive performance and is a high-performance environmentally friendly polymer waterproofing membrane that has developed rapidly in recent years. Due to long-term outdoor use and exposure to outdoor ultraviolet rays, the weather resistance of TPO waterproofing membrane is a very important indicator.
[0003] Generally, various antioxidants, anti-UV (ultraviolet light) additives, light stabilizers, fillers such as carbon black, TiO2, talcum powder, etc. are added to resist ultraviolet rays. These additives and fillers generally absorb UV light and convert it into heat energy, thereby reducing the damage to polymer materials. However, after UV light is converted into heat energy, it is easy to increase the temperature of the material and accelerate the aging of the TPO system.
[0004] Therefore, it is necessary to develop a better method for improving the weather resistance of TPO waterproof membranes, slowing down the temperature rise of TPO systems, and slowing down the aging of TPO systems. Summary of the invention
[0005] In order to solve the problems in the prior art, the present invention proposes a masterbatch containing a down-conversion material, a TPO waterproof material, and a preparation method and application thereof. The masterbatch containing the down-conversion material of the present invention contains a down-conversion material and a light stabilizer, wherein the down-conversion material is a type of substance that converts short wavelengths into long wavelength light. Through down-conversion, UV light becomes visible light that is less harmful to polymer materials. Most of the visible light is reflected by high-refractive index fillers such as TiO2 and talcum powder, so that the temperature of the TPO material will not increase significantly. The down-conversion material added in the present invention not only resists UV but also does not increase the temperature of the TPO system, and a masterbatch of a down-conversion material with excellent comprehensive performance can be obtained, and then a TPO waterproof roll with excellent comprehensive performance can be obtained. In addition, the present invention uses a down-conversion material to convert UV light into visible light, and then uses a high-refractive index filler to reflect the light. There is a certain synergistic effect between the down-conversion material and the high-refractive index filler, and it is not a simple addition of the down-conversion material and the filler.
[0006] One of the objects of the present invention is to provide a masterbatch containing a down-conversion material, wherein the masterbatch containing the down-conversion material comprises raw materials of the following components:
[0007] Polyolefins;
[0008] Down-conversion material: the down-conversion material has a maximum absorption of incident radiation in the spectral range of 280-500nm and a maximum emission of radiation in the spectral range of 400-900nm, or the down-conversion material has a maximum absorption of electromagnetic radiation in the spectral range of 300-500nm and a maximum emission of electromagnetic radiation in the spectral range of 400-600nm;
[0009] High refractive index filler: the refractive index of the high refractive index filler is at least greater than 1.5;
[0010] Light stabilizer.
[0011] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0012]
[0013] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0014]
[0015] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0016] Polyolefin 65-75wt%;
[0017] Down conversion material 0.06-1wt%;
[0018] Filler 24-32wt%;
[0019] Light stabilizer 0.5-1.5wt%.
[0020] In the present invention, the polyolefin may be 48, 50, 55, 60, 65, 70, 75, 80, 85, 90, 94 wt%;
[0021] The down conversion material can be 0.01, 0.02, 0.04, 0.06, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 wt%;
[0022] The filler can be 5, 10, 15, 20, 23, 24, 25, 30, 32, 35, 40, 45, 50 wt%;
[0023] The light stabilizer can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 wt%.
[0024] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0025] The polyolefin is selected from at least one of thermoplastic polyolefin and polyethylene; and / or,
[0026] The refractive index of the high refractive index filler is at least greater than 2; preferably, the filler is selected from at least one of titanium dioxide, TiO2 or talc.
[0027] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0028] The down-conversion material is selected from at least one of nanoparticles containing photoluminescent lanthanide cation compounds, quantum dots of semiconductor nanocrystal compounds, or organic luminescent down-conversion materials and their derivatives;
[0029] Preferably,
[0030] The photoluminescent lanthanide cations in the nanoparticles containing the photoluminescent lanthanide cation compound are selected from at least one of La, Ce, Pr, Eu, Nd, Pm, Sm, Tb, Dy, Ho, Er, Tm or Yb cations; and / or,
[0031] The organic light-emitting down-conversion material and its derivatives are selected from at least one of rhodamine, coumarin, rubrene, AlQ3 (tris(8-hydroxyquinoline)aluminum), TPD (N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine), dinaphthylidene dye, naphthalene, carbonic acid, anthrone violet, or isoanthrone violet.
[0032] Further preferably, the isoanthraquinone violet is selected from Lumogen F violet 570; the perylene dye is selected from Lumogen F yellow 083;
[0033] More preferably, the organic luminescent down conversion material is selected from Lumogen F Purple 570 and Lumogen F Yellow 083; and more preferably, the mass ratio of Lumogen F Purple 570 and Lumogen F Yellow 083 is 1:1.
[0034] The selection of down-conversion materials has a certain impact on the anti-UV effect, system temperature and mechanical properties of the final product. Among them, Lumogen F Purple 570 and Lumogen F Yellow 083 have a synergistic effect when used together. The two can better reduce the temperature of the TPO system and slow down the aging of the TPO system.
[0035] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0036] The quantum dots of the semiconductor nanocrystal compound are selected from at least one of the quantum dots of the following compounds:
[0037] Compounds formed by elements of Group 2 and Group 16 of the Periodic Table, preferably including binary compounds of MgO, MgS, MgSe, MgTe, CaO, CaS, CaTe, SrO, SrS, SrSe, SrTe, BaO, BaS, BaSe or BaTe;
[0038] Compounds formed by elements of Group 12 and Group 16 of the periodic table preferably include binary compounds and / or ternary compounds; wherein the binary compound is selected from: CdO, CdSe, CdTe, ZnO, ZnS, ZnSe or ZnTe; the ternary compound is selected from: CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, CdZnS, CdZnSe or CdZnTe;
[0039] Compounds formed by elements of Group 13 and Group 15 of the periodic table preferably include binary compounds and / or ternary compounds; wherein the binary compound is selected from: GaN, GaP, GaAs, GaSb, InP, InAs or InSb; the ternary compound is selected from: GaNP, GaNAs, GaNSb, GaPAs, GaPSb, InNP, InNAs, InNSb, InPAs, InPSb or GaAlNP;
[0040] Compounds formed by elements of Group 14 and Group 16 of the periodic table preferably include binary compounds and / or ternary compounds; wherein the binary compound is selected from: PbO, PbO2, PbS, PbSe, PbTe, SnS, SnSe, SnTe, SiO2, GeO2 or SnO2; the ternary compound is selected from: PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe or SnPbTe;
[0041] The compounds of elements of Group 14 of the periodic table preferably include monovalent compounds and / or binary compounds; wherein the monovalent compounds are selected from: Si or Ge; and the binary compounds are selected from: SiC or SiGe.
[0042] In the masterbatch containing the down-conversion material of the present invention, preferably,
[0043] The light stabilizer is a substance having a transmittance of at least 40% in the ultraviolet wavelength range of 280-380nm;
[0044] Preferably,
[0045] The light stabilizer compound has a molecular weight of at least 500 AMU (atomic mass unit), more preferably at least 1000 AMU, a higher molecular weight will slow down the migration of the additive in field applications;
[0046] Further preferably, the light stabilizer is selected from at least one of a hindered amine light stabilizer, an excited state quencher, a hydroperoxide decomposer, a free radical scavenger, or a phosphorus-containing stabilizer compound; preferably a hindered amine light stabilizer ("HALS"), which can provide stabilization without blocking or absorbing the transmission of radiation of the target wavelength;
[0047] Further preferably, the light stabilizer is selected from at least one of Cyasorb UV-1084 ([2,2-thiobis(4-tert-octylphenolato (pheonlato)]-n-butylamine, nickel), Cyasorb UV-2908 (3,5-di-tert-butyl-4-hydroxybenzoic acid, hexadecyl ester), Cyasorb 3346, Cyasorb 3529, Chimassorb 944LD, Tinuvin 622, Univul 4050, Univul 5050, Hostavin N30, Chimassorb 119, Weston 399, TNPP, P-168 or Doverphos 9228; some suitable preferred light stabilizers are shown in Table 1 below:
[0048] Table 1 – Light Stabilizers
[0049]
[0050]
[0051] In the present invention, the light stabilizer can provide stabilization without blocking or absorbing the transmission of radiation of the target wavelength. The light stabilizer mainly removes free radicals generated in the thermoplastic polymer by ultraviolet radiation, which would otherwise cause polymer degradation processes. This can be explained by the formation of nitroxyl radicals through a process known as the Denisov Cycle, in which nitroxyl radicals (RO·) combine with free radicals in the polymer. Generally, the light stabilizer does not absorb electromagnetic radiation of wavelengths in the range of UVA (320 nm to 380 nm) or UVA and UVB (280 nm to 320 nm) in large amounts, which electromagnetic radiation can be down-converted using one or more of the above-mentioned down-conversion materials.
[0052] In addition, the light stabilizer of the present invention is coordinated with the down conversion material, wherein the light stabilizer should be coordinated with the expected UV down conversion performance. Generally speaking, UV absorbers that may adversely affect down conversion should be avoided.
[0053] The light stabilizer of the present invention also has a synergistic effect with the down-conversion material. Another powerful characteristic of the light stabilizer compound is that the light stabilizer has polar-polar interaction and / or hydrogen bonding with the down-conversion material. This will slow down the migration of the down-conversion material and the ultraviolet additive in the polymer matrix, improve the ultraviolet stability of the down-conversion material and / or the dispersibility of the additive in certain thermoplastic polymers (especially polyolefins), thereby better reducing the temperature of the TPO coil and improving the anti-aging performance of the TPO coil.
[0054] The second object of the present invention is to provide a method for preparing a masterbatch containing a down-conversion material as described in one of the objects of the present invention, wherein raw materials including polyolefin, down-conversion material, filler and light stabilizer are melt-blended to obtain the masterbatch containing the down-conversion material.
[0055] In the method for preparing the masterbatch containing the down-conversion material of the present invention, the melt blending is kneaded at 13-140° C. for 2-5 min, and then further kneaded at 175-185° C. for 1-2 min.
[0056] The third object of the present invention is to provide a use of a masterbatch containing a down-conversion material as described in one of the objects of the present invention in the preparation of a TPO waterproof material; preferably, the use of the masterbatch in the preparation of a TPO waterproof membrane.
[0057] A fourth object of the present invention is to provide a TPO waterproof material, comprising the masterbatch containing the down-conversion material as described in one of the objects of the present invention.
[0058] The TPO waterproof material of the present invention comprises:
[0059]
[0060] The antioxidant of the present invention is an existing commonly used antioxidant.
[0061] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0062] Compared with the prior art, the present invention has the following advantages:
[0063] The masterbatch containing down-conversion material of the present invention contains down-conversion material and light stabilizer, wherein the down-conversion material is a kind of substance that can convert short wavelength into long wavelength light, and through down-conversion, UV light becomes visible light that is less harmful to polymer materials. Most of the visible light is reflected by high-refractive index fillers such as TiO2 and talcum powder, so that the temperature of the TPO material will not increase significantly. The down-conversion material added in the present invention not only resists UV but also does not increase the temperature of the TPO system, and a masterbatch of down-conversion material with excellent comprehensive performance can be obtained, and then a TPO waterproofing coiled material with excellent comprehensive performance can be obtained. In addition, the present invention uses down-conversion material to convert UV light into visible light, and then uses high-refractive index filler to reflect the light. There is a certain synergistic effect between the down-conversion material and the high-refractive index filler, and it is not a simple addition of down-conversion material and filler. DETAILED DESCRIPTION
[0064] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0065] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0066] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0067] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0068] Example 1
[0069] Formula and preparation method of TPO masterbatch 1 containing down-conversion material:
[0070]
[0071] The polyolefin TPO (NS06, Wuhan Petrochemical, melting point 142°C), the down-conversion material Lumogen F Purple 570 (isoanthrone violet, BASF), the high-refractive filler titanium dioxide (R015, refractive index 2.73, DuPont), and the light stabilizer UV3529 (hindered amine light stabilizer, Junlong Company) were mixed evenly, and the mixture was added to an internal mixer, mixed at 135°C for 3 minutes, and then further mixed at 180°C for 1 minute; ~2 kg of TPO masterbatch 1 containing the down-conversion material was obtained.
[0072] The preparation process of the present invention comprises the following steps: firstly preparing a TPO master batch containing a down-conversion material, and then adding the master batch into a specific formula to prepare a TPO special material.
[0073] Formula and preparation method of TPO special material sample:
[0074]
[0075] Polypropylene (PP9302, melting point 142°C, Yanshan Petrochemical; the function is to provide material rigidity and heat resistance), EPDM (Keltan3050, 51ML (ML is Mooney viscosity), Lanxess, Germany), talcum powder (YS103, 3000 mesh, Langfang Giti), TPO masterbatch 1 containing down-conversion material, antioxidant (main antioxidant (Irganox 1010, BASF) and auxiliary antioxidant (Irganox 168, BASF) are mixed in a mass ratio of 1:1) according to the above formula, and melt-extruded and granulated using a twin-screw extruder at (temperature 190°C, main engine speed 200rpm). A ~2kg TPO special material sample 1 is obtained.
[0076] Example 2
[0077] Formula and preparation method of TPO masterbatch 2 containing down-conversion material:
[0078]
[0079] The masterbatch preparation method is the same as in Example 1; ~2 kg of TPO masterbatch 2 containing down-conversion material is obtained.
[0080] Formula and preparation method of TPO special material sample:
[0081]
[0082]
[0083] The method for preparing the TPO special material sample is the same as in Example 1. A 2 kg TPO special material sample 2 is obtained.
[0084] Example 3
[0085] Formula and preparation method of TPO masterbatch 3 containing down-conversion material:
[0086]
[0087] Lumogen F Yellow 083 is a down-conversion material (L083, perylene dye, BASF). The masterbatch preparation method is the same as in Example 1; and ~2 kg of TPO masterbatch 3 containing the down-conversion material is obtained.
[0088] Formula and preparation method of TPO special material samples:
[0089]
[0090] The method for preparing the TPO special material sample is the same as in Example 1. A 2 kg TPO special material sample 3 is obtained.
[0091] Example 4
[0092] Formula and preparation method of TPO masterbatch 3 containing down-conversion material:
[0093]
[0094] Lumogen F Yellow 083 is a down-conversion material (L083, perylene dye, BASF). The masterbatch preparation method is the same as in Example 1; ~2 kg of TPO masterbatch 4 containing the down-conversion material is obtained.
[0095] Formula and preparation method of TPO special material samples:
[0096]
[0097] The method for preparing the TPO special material sample is the same as in Example 1. A 2 kg TPO special material sample 4 is obtained.
[0098] Comparative Example 1
[0099] Formula and preparation method of TPO masterbatch D-1 containing UV light stabilizer:
[0100] TPO 69.00wt%
[0101] Titanium dioxide 30wt%
[0102] UV531 1.00wt%
[0103] UV531 is a light stabilizer (ultraviolet light absorber, Lianlong). The masterbatch preparation method is the same as in Example 1; and 2 kg of TPO masterbatch D-1 containing UV light stabilizer is obtained.
[0104] Formula and preparation method of TPO special material samples:
[0105]
[0106] The method for preparing the TPO special material sample is the same as in Example 1. 2 kg of TPO special material sample D-1 is obtained.
[0107] Comparative Example 2
[0108] Formula and preparation method of TPO masterbatch D-2 containing UV light stabilizer:
[0109] TPO 68.00wt%
[0110] Titanium dioxide 30wt%
[0111] UV3529 2.00wt%
[0112] The masterbatch preparation method is the same as in Example 1; ~2 kg of TPO masterbatch D-2 containing UV light stabilizer is obtained. The formula and preparation method of the TPO special material sample:
[0113]
[0114] The method for preparing the TPO special material sample is the same as in Example 1. A 2 kg TPO special material sample D-2 is obtained.
[0115] Comparative Example 3
[0116] Formula and preparation method of TPO masterbatch D-3 containing UV light stabilizer:
[0117]
[0118] The masterbatch preparation method is the same as in Example 1; ~2 kg of TPO masterbatch D-3 containing UV light stabilizer is obtained. The formula and preparation method of the TPO special material sample:
[0119]
[0120] The method for preparing the TPO special material sample is the same as in Example 1. 2 kg of TPO special material sample D-3 is obtained.
[0121] Comparative Example 4
[0122] Formula and preparation method of TPO masterbatch D-4 containing down-conversion material:
[0123] TPO 69.92wt%
[0124] Lumogen F Purple 570 (L570) 0.08wt%
[0125] Titanium dioxide 30wt%
[0126] The masterbatch preparation method is the same as in Example 1; ~2 kg of TPO masterbatch D-4 containing down-conversion material is obtained.
[0127] Formula and preparation method of TPO special material sample:
[0128]
[0129] The method for preparing the TPO special material sample is the same as in Example 1. 2 kg of TPO special material sample D-4 is obtained.
[0130] Test method:
[0131] The artificial climate accelerated aging test of exposed waterproof materials should be carried out with a xenon arc lamp, and the cumulative irradiation energy at a wavelength of 340nm should not be less than 5040KJ / (m 2 ·nm), the cumulative radiation energy of the exposed single-layer waterproof membrane should not be less than 10080KJ / (m 2 ·nm), the mechanical properties of the material after aging test shall not show cracking, delamination, blistering, bonding and holes.
[0132] The material surface temperature change is the difference between the surface temperature after 8 hours of irradiation and the initial reference temperature.
[0133] The down-conversion materials, UV light stabilizer content, and performance test results of the special material samples prepared in the above embodiments and comparative examples are shown in Table 2.
[0134] Table 2
[0135]
[0136]
[0137] From the results in Table 2, we can see that:
[0138] From the results of Examples 1-4, it can be seen that the temperature rise of the TPO containing the down-conversion material of the present invention is less, which is very helpful in reducing material aging and the covered building system; however, the content of the down-conversion material has a certain influence on the temperature drop of the TPO.
[0139] From the comparison results of Example 2, Example 3 and Example 4, it can be seen that the combination of two down-conversion materials with complementary wavelengths (violet L570 and yellow L083) has a synergistic effect, which can better reduce the temperature of the TPO system and slow down the aging of the TPO system.
[0140] From the comparison results of Example 2, Comparative Example 2 and Comparative Example 4, it can be seen that L570 and UV3529 also have a synergistic effect, that is, the combined use of the down-conversion material and the hindered amine light stabilizer can also better reduce the temperature of the TPO system and slow down the aging of the TPO system.
[0141] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0142] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0143] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0144] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. A masterbatch containing a down-conversion material, characterized in that: The masterbatch containing the down-conversion material comprises raw materials of the following components: Polyolefins; Down-conversion material: the down-conversion material has a maximum absorption of incident radiation in the spectral range of 280-500nm and a maximum emission of radiation in the spectral range of 400-900nm, or the down-conversion material has a maximum absorption of electromagnetic radiation in the spectral range of 300-500nm and a maximum emission of electromagnetic radiation in the spectral range of 400-600nm; High refractive index filler: the refractive index of the high refractive index filler is at least greater than 1.5; Light stabilizer.
2. The masterbatch containing down-conversion material according to claim 1, characterized in that:
3. The masterbatch containing down-conversion material according to claim 2, characterized in that:
4. The masterbatch containing down-conversion material according to claim 1, characterized in that: The polyolefin is selected from at least one of thermoplastic polyolefin and polyethylene; and / or, The refractive index of the high refractive index filler is at least greater than 2; preferably, the filler is selected from at least one of titanium dioxide, TiO2 or talc.
5. The masterbatch containing down-conversion material according to claim 1, characterized in that: The down-conversion material is selected from at least one of nanoparticles containing photoluminescent lanthanide cation compounds, quantum dots of semiconductor nanocrystal compounds, or organic luminescent down-conversion materials and their derivatives; Preferably, The photoluminescent lanthanide cations in the nanoparticles containing the photoluminescent lanthanide cation compound are selected from at least one of La, Ce, Pr, Eu, Nd, Pm, Sm, Tb, Dy, Ho, Er, Tm or Yb cations; and / or, The organic luminescent down-conversion material and its derivatives are selected from at least one of rhodamine, coumarin, rubrene, AlQ3, TPD, perylene dye, naphthalene, carbonic acid, anthrone violet, or isoanthrone violet; Further preferably, the isoanthraquinone violet is selected from Lumogen F violet 570; the perylene dye is selected from Lumogen F yellow 083; More preferably, the organic luminescent down conversion material is selected from Lumogen F Purple 570 and Lumogen F Yellow 083.
6. The masterbatch containing down-conversion material according to claim 5, characterized in that: The quantum dots of the semiconductor nanocrystal compound are selected from at least one of the quantum dots of the following compounds: Compounds formed by elements of Group 2 and Group 16 of the Periodic Table, preferably including binary compounds of MgO, MgS, MgSe, MgTe, CaO, CaS, CaTe, SrO, SrS, SrSe, SrTe, BaO, BaS, BaSe or BaTe; Compounds formed by elements of Group 12 and Group 16 of the Periodic Table of Elements, preferably including binary compounds and / or ternary compounds; Wherein, the binary compound is selected from: CdO, CdSe, CdTe, ZnO, ZnS, ZnSe or ZnTe; the ternary compound is selected from: CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, CdZnS, CdZnSe or CdZnTe; Compounds formed by elements of Group 13 and Group 15 of the periodic table preferably include binary compounds and / or ternary compounds; wherein the binary compound is selected from: GaN, GaP, GaAs, GaSb, InP, InAs or InSb; the ternary compound is selected from: GaNP, GaNAs, GaNSb, GaPAs, GaPSb, InNP, InNAs, InNSb, InPAs, InPSb or GaAlNP; Compounds formed by elements of Group 14 and Group 16 of the periodic table preferably include binary compounds and / or ternary compounds; wherein the binary compound is selected from: PbO, PbO2, PbS, PbSe, PbTe, SnS, SnSe, SnTe, SiO2, GeO2 or SnO2; the ternary compound is selected from: PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe or SnPbTe; The compounds of elements of Group 14 of the periodic table preferably include monovalent compounds and / or binary compounds; wherein the monovalent compounds are selected from: Si or Ge; and the binary compounds are selected from: SiC or SiGe.
7. The masterbatch containing down-conversion material according to claim 1, characterized in that: The light stabilizer is a substance having a transmittance of at least 40% in the ultraviolet wavelength range of 280-380nm; Preferably, The light stabilizer compound has a molecular weight of at least 500 AMU, more preferably at least 1000 AMU; Further preferably, the light stabilizer is selected from at least one of a hindered amine light stabilizer, an excited state quencher, a hydroperoxide decomposer, a free radical scavenger or a phosphorus-containing stabilizer compound.
8. A method for preparing a masterbatch containing a down-conversion material according to any one of claims 1 to 7, characterized in that: Raw materials including polyolefin, down conversion material, filler and light stabilizer are melt-blended to obtain the master batch containing the down conversion material.
9. Use of the masterbatch containing the down-conversion material as claimed in any one of claims 1 to 7 in the preparation of TPO waterproof materials; preferably in the preparation of TPO waterproof membranes.
10. A TPO waterproof material, characterized in that: The invention comprises a masterbatch containing a down-conversion material as described in any one of claims 1 to 7.